A Novel Presenilin 1 Mutation in Early-Onset Alzheimer's Disease With Prominent Frontal Features. (August 2014) - Nygaard, Haakon B.; Lippa, Carol F.; Mehdi, Djekidel; Baehring, Joachim M.
Familial Alzheimer's disease (AD) is a rare disorder involving known autosomal dominant mutations in the amyloid precursor protein and presenilin (PSEN) 1 and 2. Here, we present a case of early-onset AD with prominent frontal features associated with a novel deletion of codon 40 in the PSEN1 gene. Serial brain magnetic resonance imaging and 18 F florbetapir imaging show prominent involvement of the frontal lobes, corresponding with the clinical presentation. This case report illustrates a possible link between a novel PSEN1 mutation and frontal variant AD.